The Transformation of Balinese Customary Law in Addressing Human Rights Challenges: A Socio-Legal Perspective (Contrarius Series: Law & Social Justice, 2026)
Balinese customary law (hukum adat Bali) represents a unique socio-legal system rooted in the indigenous philosophy of Tri Hita Karana, which harmonizes the relationship between humans, nature, and the divine. While its communal and restorative character has historically maintained social cohesion, the evolving global discourse on human rights introduces both challenges and opportunities for transformation. This study explores the transformation of Balinese customary law in response to human rights concerns, particularly regarding equality, non-discrimination, gender justice, and individual autonomy. Employing a socio-legal perspective, it examines how traditional institutions such as desa adat, paruman adat, and awig-awig adapt to contemporary legal and moral standards. Findings indicate that transformation occurs through interpretive flexibility, community dialogue, and state recognition, revealing a dynamic interaction between local wisdom and universal human rights norms